(2x+8)(x-3)=154

Simple and best practice solution for (2x+8)(x-3)=154 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+8)(x-3)=154 equation:


Simplifying
(2x + 8)(x + -3) = 154

Reorder the terms:
(8 + 2x)(x + -3) = 154

Reorder the terms:
(8 + 2x)(-3 + x) = 154

Multiply (8 + 2x) * (-3 + x)
(8(-3 + x) + 2x * (-3 + x)) = 154
((-3 * 8 + x * 8) + 2x * (-3 + x)) = 154
((-24 + 8x) + 2x * (-3 + x)) = 154
(-24 + 8x + (-3 * 2x + x * 2x)) = 154
(-24 + 8x + (-6x + 2x2)) = 154

Combine like terms: 8x + -6x = 2x
(-24 + 2x + 2x2) = 154

Solving
-24 + 2x + 2x2 = 154

Solving for variable 'x'.

Reorder the terms:
-24 + -154 + 2x + 2x2 = 154 + -154

Combine like terms: -24 + -154 = -178
-178 + 2x + 2x2 = 154 + -154

Combine like terms: 154 + -154 = 0
-178 + 2x + 2x2 = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(-89 + x + x2) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-89 + x + x2)' equal to zero and attempt to solve: Simplifying -89 + x + x2 = 0 Solving -89 + x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '89' to each side of the equation. -89 + x + 89 + x2 = 0 + 89 Reorder the terms: -89 + 89 + x + x2 = 0 + 89 Combine like terms: -89 + 89 = 0 0 + x + x2 = 0 + 89 x + x2 = 0 + 89 Combine like terms: 0 + 89 = 89 x + x2 = 89 The x term is x. Take half its coefficient (0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. x + 0.25 + x2 = 89 + 0.25 Reorder the terms: 0.25 + x + x2 = 89 + 0.25 Combine like terms: 89 + 0.25 = 89.25 0.25 + x + x2 = 89.25 Factor a perfect square on the left side: (x + 0.5)(x + 0.5) = 89.25 Calculate the square root of the right side: 9.447221814 Break this problem into two subproblems by setting (x + 0.5) equal to 9.447221814 and -9.447221814.

Subproblem 1

x + 0.5 = 9.447221814 Simplifying x + 0.5 = 9.447221814 Reorder the terms: 0.5 + x = 9.447221814 Solving 0.5 + x = 9.447221814 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = 9.447221814 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = 9.447221814 + -0.5 x = 9.447221814 + -0.5 Combine like terms: 9.447221814 + -0.5 = 8.947221814 x = 8.947221814 Simplifying x = 8.947221814

Subproblem 2

x + 0.5 = -9.447221814 Simplifying x + 0.5 = -9.447221814 Reorder the terms: 0.5 + x = -9.447221814 Solving 0.5 + x = -9.447221814 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = -9.447221814 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = -9.447221814 + -0.5 x = -9.447221814 + -0.5 Combine like terms: -9.447221814 + -0.5 = -9.947221814 x = -9.947221814 Simplifying x = -9.947221814

Solution

The solution to the problem is based on the solutions from the subproblems. x = {8.947221814, -9.947221814}

Solution

x = {8.947221814, -9.947221814}

See similar equations:

| H=16t(7-t)+10 | | 3t^6*3t^2= | | 6c=11 | | -46=-6x+2 | | Sin^2(x)-sin(x)-1=0 | | 6(x-4)+10=2x-12 | | 115x+25+10x=1400 | | 11=-3-x | | 4v=7 | | 2(m-3)-(2m+6)= | | 9c+8=3 | | x+(x+7)=60 | | N^2-9n+19=0 | | -11=4-8x+1 | | 5n-7=4 | | 48=x^4-5x^2+4 | | 8b+11+2b=2b+2 | | 2(x+2)=16+4x | | 2y=(k+4)x-1 | | 2=8(h-5) | | 0.8+0.4=12 | | 0.8x=0.4 | | 2=3(i-5) | | -9=6a+1-a | | 18.4+8=t | | 3(x-5)=5x-(3-y) | | 3(7x+3)-11(2x+1)=-x-2 | | 0=6x^2+6x-120 | | 4n+3=-12 | | 9=3k-5 | | .5x+42=50 | | 18-w-13=-20 |

Equations solver categories